2018
DOI: 10.1111/cpr.12431
|View full text |Cite
|
Sign up to set email alerts
|

Oroxylin A inhibits ethanol‐induced hepatocyte senescence via YAP pathway

Abstract: Therefore, these aggregated data suggested that oroxylin A relieved alcoholic liver injury possibly by inhibiting the senescence of hepatocyte, which was dependent on its activation of YAP in hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Finally, metformin, a potential anti-aging agent, activated the YAP-CDK6 pathway and suppressed D-gal-induced senescence of C6 cells. Our implication of the YAP-CDK6 pathway in senescence is in line with recent observations that have demonstrated that YAP controls senescence of IMR90 cells [ 24 ], human mesenchymal stem cells [ 44 ], hepatocytes [ 45 ], and YAP-1 deficiency promotes health ageing of Caenorhabditis elegans [ 46 ]. Moreover, some other YAP-targeted genes, such as CYR61 (Cysteine Rich Angiogenic Inducer 61) and CTGF (Connective Tissue Growth Factor), are also reported to be involved in cellular senescence [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 89%
“…Finally, metformin, a potential anti-aging agent, activated the YAP-CDK6 pathway and suppressed D-gal-induced senescence of C6 cells. Our implication of the YAP-CDK6 pathway in senescence is in line with recent observations that have demonstrated that YAP controls senescence of IMR90 cells [ 24 ], human mesenchymal stem cells [ 44 ], hepatocytes [ 45 ], and YAP-1 deficiency promotes health ageing of Caenorhabditis elegans [ 46 ]. Moreover, some other YAP-targeted genes, such as CYR61 (Cysteine Rich Angiogenic Inducer 61) and CTGF (Connective Tissue Growth Factor), are also reported to be involved in cellular senescence [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, restriction of HSC contraction represents a novel intervention strategy for liver fibrosis or cirrhosis, as well as portal hypertension. We recently reported that oroxylin A had significant antifibrotic and hepatoprotective effects in vitro and in vivo [17, 31, 32], and observed that oroxylin A could improve sinusoidal vascular remodeling [27]. These observations directed us to investigate whether modulation of HSC contractile phenotype was involved in oroxylin A’s effects.…”
Section: Discussionmentioning
confidence: 99%
“…Oroxylin A can restore the deceased cell viability and increased expression of senescence makers in ethanol‐treated hepatocytes. And this protective role of oroxylin A is associated with activation of the YAP pathway, because YAP inhibitor or YAP knockdown significantly disturbed its function (Jin et al, ). In addition, oroxylin A prevents ethanol‐induced lipid accumulation by regulating genes implicated in lipid metabolism (Jin et al, ).…”
Section: Natural Compounds Beneficial For Ald Treatmentmentioning
confidence: 99%